The regulatory enterprise government, regulation, and legitimacy - Prosser, Tony. (Oxford : Oxford University Press, 2010)
The use of regulation to control behaviour is a defining feature of modern government, penetrating a wide range of social & economic life, from health & social care to transport & environmental protection. This book offers a detailed study of how regulation works in practice.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Administrative agencies -- Great Britain